Avaliação do comportamento bacteriano e alterações sensoriais em tilápias do Nilo (Oreochromis niloticus) durante estocagem em gelo - Leite, Lana Oliveira (2013)
Fish is a food susceptible to deterioration due their intrinsic characteristics, requiring bacterial monitoring in postmortem storage. Thus, the objective was to quantify mesophilic, psychrotrophic, psychrophilic bacteria in Nile tilapia (Oreochromis niloticus) during to 21 days of storage under the action of ice at temperature refrigeration. Four experiments were conducted, separated to two groups, gutted and ungutted, with eight samples totaling 32 samples. Every three days was taken a exemplar of tilapia for analyzes of the trial: sensory evaluation according to the Quality Index Method (QIM) adapted to the Nile tilapia and heterotrophic bacterial count of cultivable. In sensory analysis of raw fish attributes were assessed: general appearance, eyes, gills, muscles and texture of the fish, according to the Sensory Characters Sum (S.C.S). To each specimen were quantified bacterial groups: psychrophilic (23 °C), psychrotrophic (7 °C) and mesophilic (35 °C), the surface and the muscle, using the method of standard plate count (SPC). There was no statistical difference between the three bacterial groups analyzed the significance level of 5% within the same treatments and between groups. The storage time was highly correlated with the counting of bacterial groups and increased QIM for both eviscerated fish, and for those not drawn. It was considered that the process of evisceration on the premises of the fish did not increase its useful life. It is suggested, therefore, greater attention in the process of gutting fish markets that sell live fish, because this process was not carried out effectively to security and recovery product.